Assessing the public-private partnership handover: Experience from China's water sector. (February 2023) - Bao, Fengyu; Martek, Igor; Chan, Albert P.C.; Chen, Chuan; Yang, Yang; Yu, Heng
Abstract: Most infrastructure public-private partnerships (PPPs) are returned to the government once the contract term expires. Before the handover, a preparatory period, known as the "handover stage (HS), " is needed to determine whether the project is fit for handover. However, to date, no means to assess the performance status of the handover management has been established. This study addresses this practical demand by establishing a definition of handover success and identifying and evaluating criteria for the measurement of handover success, which contributes to a better understanding of HS management. Highlights: PPP handover success is defined as a hierarchical structure constituted by 12 key performance indicators. 'Consecutive water production' emerges as the indicator with highest efficacy in assessing handover success of water PPPs. Governments should be vigilant when dealing with handover stage due to the opportunistic tendency of private parties. A process-based handover performance assessment mode comprising three evaluation nodes is proposed.